Detection of Histoplasma capsulatum in Guano of House Bats in Bucaramanga, Santander - Torres, María Y.; Rodríguez Rodríguez, Edgar Daniel; Quintero S., Vladimir; Rodríguez-Moreno, Raúl; Castellanos Torres, Vilma; Álvarez, Yenny L.; Carvajal, Paola A.; Fernández, Alexánder; González, Ferley; Gutiérrez, Leonardo; César; Ramírez, Néstor; et al. (Spei Domus, 2012)
A total of 50 dwellings were examined to establish the presence of the Histoplasma capsulatum fungus in guano, with the aim of determining the relationship between the presence of the fungus, the environmental conditions of the shelter and the bat species present. There was no evidence of the presence of H. capsulatum by direct observation and Sabouraud agar plating with Oxytetracycline, but there was evidence of fungi that are important for human health, such as Aspergillus sp., Penicillium sp., Rhizopus sp., Mucor sp. and Oospora sp. Three species of bats were identified, Molossus molossus being the most frequent, followed by individuals of the genus Artibeus sp. and a lesser extent Glossophaga soricina. It was found that temperature and humidity conditions of the shelters most used by bats have asbestos cement roofs and styrofoam ceilings or clay roofs in polystyrene ceilings. These materials create an attractive interior environment that is exploited mainly by the Molossus molossus and Glossophaga soricina, unlike the genus Artibeus that preferred open sites. We recommend further studies and testing with other diagnostic techniques because the negative results for the presence of H. capsulatum do not necessarily; also to intensify research to determine any possible risks to human health from the other fungi found during the study. The project was carried out by the developed by the Veterinary Medicine and Zootechnics Faculty at the Universidad Cooperativa de Colombia, by the Animal Science Research Group (Grica) epidemiology research line.